CATEGORY SHIFTS IN TRANSLATING ENGLISH COMPLEX NOUN PHRASES IN UGLY LOVE NOVEL INTO INDONESIAN - Sunarti Desrieny Tambunan (Universitas Gunadarma, 2022)
English noun phrases can be categorized into simple and complex noun phrases. Whether or not a noun phrase is complex, it can be seen from the structure of a noun phrase that has a pre-modification, head, and post-modification or its complementation. However, when it is translated into Indonesian, the shifts happen. In translations, there are two types of shifts. They are level shifts and category shifts. This research is aimed at finding out the complex noun phrases in a novel entitled Ugly Love and their category shifts of translation in Indonesian. A descriptive qualitative method was applied in this research. Based on the findings, there are 41 Complex Noun Phrases found. However, there are six (6) Complex Noun Phrases that are translated using category shifts. Two (2) data are translated using structure shift and unit shift. One (1) data is translated using unit shift. One (1) data is translated using unit shift and class shift. Two (2) data are translated using structure shift, class shift, and unit shift. It reveals that the most dominant used of category shift is unit shift, followed by structure shift. Furthermore, the least used of category shift is class shift. In addition, intra-system shift was not found because the nouns mentioned in the data findings are all singular nouns.